(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2019)
The research work deals with the approaches of Barthes and Saussure to literature. Barthes and Saussure view literature as "self-contained autonomous body", consisting of a set of syntactical and linguistic components, such as the phonemes, morphemes, allophones, morphs, hyponyms and antonyms. Other considerations, as components of literature, such as author, the historical context of the text, the various social, religious or cultural truths implicit in the text, are all to be ignored. This is because literature is an autonomous body, independent of any other factors alien to its linguistic nature: the writer accordingly, has no role to play or anything to do in the text except assembling or redeploying a set of already existing linguistic and cultural structures into a unified whole . The work highlights those views of Barthes and Saussure which dehumanize literature, and claim the death of the author, pointing out the dangers of breaking up the text’s "logocentrism". It also questions their concepts about stretching the text’s interpretive limits endlessly and the ability of the reader to assimilate the infinite processes of the interpretations. The work, however, concludes that the practice of literary criticism cannot be said to be, according to a Barthean or Saussurean formula, "iconoclastic", or "monolithic", but rather it should be concrete, "because it is the concentration of many determinations", the least of which can never be ignored. يعالج البحث مفهوم سوسور وبارت اللغوي في تحليل الأدب ودراسته نقدياً. ينظر بارت وسوسور إلى الأدب بوصفه هيئة مستقلة ذاتياً قائمة بحد ذاتها, قوامها اللغة بمكوناتها الأساسية المعروفة النحوية والصرفية, بما في ذلك الحروف, والكلمات, والمقاطع الصوتية, وعلامات الاسم, والصفة, والفعل, فضلا عن البنى المختلفة التي تشكّل الجمل الاسمية والفعلية, والشرطية, وأشباه الجمل . ويختلف دوسوسور مع بارت حول مفهوم الدال والمدلول (signifier/signified), حيث يعتقد دوسوسور بأنّ الدال والمدلول يشكلان وحدة إشاراتية متكاملة, بينما يعتقد بارت بأنّ الدال ينزلق باستمرار تحت المدلول, لأنّ "النص الأدبي يشكّل كوكبة من مجموعات الدال, وليس نظاماً يقوم على مجموعات المدلول". وبالتالي فإنّ قراءة النص الأدبي يجب أن تتم بمعزل عن الكاتب, أو البيئة الاجتماعية التي كتب فيها النص, أو السيرة الذاتية للمؤلف, أو أي سياق تاريخي آخر. يبرر سوسور وبارت مقولتهما تلك بالقول بأنّ النص الادبي هو مجرد وحدة لغوية متكاملة لا يسهم المؤلف فيها بشيء سوى إعادة ترتيب وتصفيف للإشارات اللغوية والأفكار الثقافية من جديد. من خلال هذا الطرح يجرّد سوسور وبارت الأدب من وظيفته الإنسانية وأبعاده الأخلاقية, وخاصة بطرحهما نظرية "موت الكاتب", وتجاهلهما علاقة النص الأدبي بالواقع المعاشي الاجتماعي للناس, وصلة المؤلف الوثيقة بهذا النص, وتركيزهما على الجانب اللغوي وحسب. ينتهي البحث إلى إبراز عيوب البنيوية ونواقصها, وتسليط الضوء على الأفكار المجردة الغامضة فيها, تلك الافكار التي تؤدي بالنص الأدبي والقارئ إلى طريق مسدود؛ كما يقدّم البحث أفكاراً بديلة تبرز دور الأدب في حياة الشعوب وتاريخها الفكري والثقافي, ودور الأديب الإبداعي, وعلاقته بالنص الأدبي, ومساهمته في إغناء ثقافة البشر وحضارتهم الانسانية.